Metabolic profile and transcriptome reveal the mystery of petal blotch formation in rose - Naizhe Ji; Qianyu Wang; Shanshan Li; Jiaxin Wen; Liangsheng Wang; Xiaohao Ding; Shiwei Zhao; Hui Feng (BMC Plant Biology, 2023)
Abstract Background Petal blotch is a unique ornamental trait in angiosperm families, and blotch in rose petal is rare and has great esthetic value. However, the cause of the formation of petal blotch in rose is still unclear. The influence of key enzyme genes and regulatory genes in the pigment synthesis pathways needs to be explored and clarified. Results In this study, the rose cultivar ‘Sunset Babylon Eyes’ with rose-red to dark red blotch at the base of petal was selected as the experimental material. The HPLC-DAD and UPLC-TQ-MS analyses indicated that only cyanidin 3,5-O-diglucoside (Cy3G5G) contributed to the blotch pigmentation of ‘Sunset Babylon Eyes’, and the amounts of Cy3G5G varied at different developmental stages. Only flavonols but no flavone were found in blotch and non-blotch parts. As a consequence, kaempferol and its derivatives as well as quercetin and its derivatives may act as background colors during flower developmental stages. Despite of the differences in composition, the total content of carotenoids in blotch and non-blotch parts were similar, and carotenoids may just make the petals show a brighter color. Transcriptomic data, quantitative real-time PCR and promoter sequence analyses indicated that RC7G0058400 (F3’H), RC6G0470600 (DFR) and RC7G0212200 (ANS) may be the key enzyme genes for the early formation and color deepening of blotch at later stages. As for two transcription factor, RC7G0019000 (MYB) and RC1G0363600 (WRKY) may bind to the promoters of critical enzyme genes, or RC1G0363600 (WRKY) may bind to the promoter of RC7G0019000 (MYB) to activate the anthocyanin accumulation in blotch parts of ‘Sunset Babylon Eyes’. Conclusions Our findings provide a theoretical basis for the understanding of the chemical and molecular mechanism for the formation of petal blotch in rose.